Chemical stress as a consequence of prolong drug use, A study on chronic health condition - Dur-e-Shahwar; Noushad , Shamoon; Kisa Fatima; Ahmed , Sadaf (International Journal of Endorsing Health Science Research, 2016)
Background: Chemical stress is an indication of increase or a lesser amount of chemicals that body has exposed both internal or external environment provided to singe cell such as pollution, smoking, ingested food additives, pesticides, excessive consumption of sugar and alcohol, too many cups of coffee and even passive smoking cause chemical stress. This prolong exposure to any affluence can cause chemical stress that interferes with body’s natural balance. Methodology: A cross sectional survey based study was conducted at a local hospital including 3 groups of patients, Group I was using only anti diabetic drugs, Group II was chronic user of cardiac medications while Group III was using both. Demographic data, medical history and drug use duration and dosage were investigated as well as intensity of Chemical stress was calculated by Sadaf stress scale. The patients with severe and psychological and mental illness or any other chronic illness or patients who were failed to provide reliable information were excluded from study. Results: The result showed that there is a stressful built-up of chemicals as a result of altered metabolism due to excess drugs use in these patients. However moderate stress is majorly reported in Group III that indicates increased number of prescribed medications and their correlation with intensity of chemical stress. However, none of the patient scored severe stress which is again an indication that there is a progressive psychophysiological deteriorating state rather than fully damaged that can be improved.